Synthesis of highly efficient azure-to-blue-emitting Zn-Cu-Ga-S quantum dots - Kim, Bu-Yong; Kim, Jong-Hoon; Lee, Ki-Heon; Jang, Eun-Pyo; Han, Chang-Yeol; Jo, Jung-Ho; Jang, Ho Seong; Yang, Heesun (ROYAL SOC CHEMISTRY, 2017)
To realize blue emission-capable non-Cd I-III-VI quantum dots (QDs), we explore the synthesis of ternary Cu-Ga-S (CGS) QDs and subsequent quaternary Zn-Cu-Ga-S (ZCGS) via Zn alloying into a CGS host. The resulting ZCGS/ZnS core/shell QDs possess not only Zn content-dependent tunable emissions in the azure-to-blue range but also exceptional quantum yields of 78-83%.
Keywords: SEMICONDUCTOR NANOCRYSTALS; OPTICAL-PROPERTIES; COLOR CONVERTERS; DIODES; DEVICES; LUMINESCENT; ELECTROLUMINESCENCE; PERFORMANCE; BRIGHT